دراسة تقابولية بين اللغة العربية واللغة الإندونيسية على مستوى النعت والاستفادة منها في تعليم اللغة العربية للمبتدئين الإندونيسيين - Saipuddin; Abdurrahman Hilabi (Rayah Al-Islam, 2018)
This study is aimed to know the adjectives between the Arabic language and Indonesian language in order to determine the similarities and differences among them in terms of morphology, syntax, and semantics, and then to predict the difficulties that will be faced by Indonesian students during the teaching activities, and then to propose a method of teaching based on the result of the contrastive study to teach Arabic language at the level of adjectives for beginner Students of Indonesian. This study uses the methodology of descriptive analysis to identify the characteristics of adjectives in Arabic and Indonesian, and then using the method of comparative analysis to compare Arabic and Indonesian language at the level of adjectives in order to obtain the similarities and differences between these both languages. The results of this research are: the first is there are similarities and differences of adjectives in Arabic and Indonesian in terms of morphology, syntax, and semantics, and the second is by this research can be used in preparing lessons and methods for teaching the Arabic language at the level of adjectives for the beginner students of Indonesian.